Sickle hemoglobinopathy research in Zimbabwe and Zambia: setting up an international sickle cell disease registry - Kuona, Patience; Kandawasvika, Gwendoline Q.; Chunda-Liyoka, Catherine; Ruredzo, Ian M.; Sambo, Pauline M.; Gorejena-Chidawanyika, Pamela; Mantina, Hamakwa M.; Mtisi, Takudzwa J.; Phiri, Cynthia; Chikara, Lawson; Kaweme, Natasha M.; Chivige, Exavior; et al. (Frontiers in Medicine, 2025)
Majority of the 500,000 children born with sickle cell disease (SCD) annually are born in Africa. SCD contributes significantly to morbidity and mortality. This is worsened by the reduced access to therapeutic plus preventive care and limited health outcomes data. To address these challenges, we aim to develop and manage a standardized electronic SCD registry, establish consistent standards of care (SoC) for patients, improve the SCD research and biobanking capacity in Zimbabwe and Zambia. This five-year program employs a multi-pronged approach that include infrastructure and skilled manpower capacity building of SCD clinics, registry, biobanking, cohort and implementation science research studies to improve SCD treatment outcomes. We are collaborating with the SickleInAfrica consortium (Ghana, Mali, Nigeria, Tanzania, Uganda, and South Africa), the African Institute of Biomedical Sciences and Technology (AiBST) and St Jude’s Children Research Hospital. We have established the SCD registry in Zimbabwe and Zambia for children and adult patients enrolling 1796 (45%) of the targeted 4,000 participants as of March 2024. We are participating in SickleInAfrica consortium research activities, training health workers and educating SCD patient communities on SoC. This collaboration with African researchers, policymakers, health workers, and SCD patient communities will improve uptake of SCD SoC and increase our research capacity.